2002
DOI: 10.1159/000067187
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia and Impulsive Behaviour in Middle Adolescence

Abstract: Background: In clinical samples, bulimia seems to be associated with various dyscontrol behaviours suggesting weakness in impulse control. Population studies of adolescents, however, are needed. We evaluated the association between self-reported bulimic behaviour and a number of dyscontrol behaviours, namely bullying, truancy, excessive drinking and sexual disinhibition among adolescents aged 14–16. This is the first study on bulimia and impulsivity in a large non-selected adolescent population sample. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
(41 reference statements)
1
42
0
2
Order By: Relevance
“…The initial measurements support previous fi ndings that girls with bullying behavior often were bullying victims themselves [23] , show relatively high violence-related behavior and sexual risk-taking behavior levels [4,5,[24][25][26] and anger levels [10,19] , in addition to disturbed interpersonal relationship patterns [11,20] . Their initial general health perceptions, vitality, social functioning, role limitations resulting from emotional problems and mental health were distinctly below normal values [8,21] .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The initial measurements support previous fi ndings that girls with bullying behavior often were bullying victims themselves [23] , show relatively high violence-related behavior and sexual risk-taking behavior levels [4,5,[24][25][26] and anger levels [10,19] , in addition to disturbed interpersonal relationship patterns [11,20] . Their initial general health perceptions, vitality, social functioning, role limitations resulting from emotional problems and mental health were distinctly below normal values [8,21] .…”
Section: Discussionsupporting
confidence: 79%
“…Analysis of the sociodemographic, psychiatric, and risk-taking behavior data permitted the two groups to be compared [5,22,23] . The initial measurements support previous fi ndings that girls with bullying behavior often were bullying victims themselves [23] , show relatively high violence-related behavior and sexual risk-taking behavior levels [4,5,[24][25][26] and anger levels [10,19] , in addition to disturbed interpersonal relationship patterns [11,20] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on a large non-selected adolescent population sample found an association between bulimic behaviours and discontrol behaviours (bullying, truancy, excessive drinking, sexual dishinibition) [105] . Moreover, according to Dawe and Loxton [106] , impulsivity seems to be a key feature of a number of axis I and II psychiatric disorders, such as EDs with binging/purging, substance use disorders and borderline personality disorder.…”
Section: Impulsivitymentioning
confidence: 99%
“…Women with bulimia nervosa (BN) have been shown to engage in disinhibited behaviors associated with high negative consequences, such as promiscuous sexual behaviors (Kaltiala-Heino, Rissanen, Rimpelae, & Rantanen, 2003). When compared with controls, women with BN have reported greater sexual activity and sexual experience (Abraham et al, 1985;Coovert, Kinder, & Thompson, 1989;Dykens & Gerrard, 1986;Irving, McCluskey-Fawcett, & Thissen, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by the fact that both increased sexual behaviors (Cooper, Wood, Orcutt, & Albino, 2003;Hoyle, Fejfar, & Miller, 2000;White & Johnson, 1988;Wulfert, Safren, Brown, & Wan, 1999) and BN (Brewerton, Hand, & Bishop, 1993;KaltialaHeino et al, 2003;Peñ as-Liedó, Vaz, Ramos, & Waller, 2002) show consistent and significant relationships with impulsivity. Likewise, studies have shown that women with BN and individuals who engage in risky sexual behavior both have increased levels of impulsivity and disinhibition (Brewerton et al, 1993;Kaltiala-Heino et al, 2003;White & Johnson, 1988;Wulfert et al, 1999). Impulsivity may, therefore, underlie observed relationships between disordered eating behaviors common to BN (i.e., binge eating and compensatory behaviors) and sexual behaviors.…”
Section: Introductionmentioning
confidence: 99%